Blastic transformation of mantle cell lymphoma with B-lymphoblastic features - David Cantu; Yuridia Alvarado; Joyce Murata-Collins; Dennis D. Weisenburger (Elsevier, 2019)
Mantle cell lymphoma is characterized by the presence of the t(11;14)(q13;q32), which is found in more than 95% of cases. We present a case of mantle cell lymphoma with the typical phenotype, which transformed to a blastic morphology with loss of expression of CD20, CD5 and BCL2, and gain of CD10 and TdT. In cases presenting with blastic morphology, the use of CD10 and TdT in addition to the usual mantle cell lymphoma markers is essential since cases of mantle cell lymphoma with B-lymphoblastic features may require innovative treatment. Keywords: Mantle cell lymphoma, B-lymphoblastic lymphoma, Transformation